2005
DOI: 10.1902/jop.2005.76.10.1743
|View full text |Cite
|
Sign up to set email alerts
|

Human Gingival Fibroblast Integrin Subunit Expression on Titanium Implant Surfaces

Abstract: These results demonstrate the presence of multiple integrin subunits in human gingival fibroblasts grown in contact with titanium implant surfaces and that titanium surface roughness alters cellular morphology but appears to have limited effects on integrin expression. This study provides insight into the complicated cellular and molecular events occurring at the implant surface that may be critical to optimizing the soft tissue interactions with the soft tissue-implant interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…It has been well indicated that integrins, whose α and β subunits constitute non-covalently linked αβ heterodimers, are responsible for cell adhesion [33]. Several integrin subunits including α2, α5, β1 and β3 were identified in the periodontal tissue [18,34]. Given the interplay of integrins with the extracellular matrix (ECM) and cytoskeleton [35], they regulate cellular functions, cell proliferation, adhesion, shape, and differentiation [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well indicated that integrins, whose α and β subunits constitute non-covalently linked αβ heterodimers, are responsible for cell adhesion [33]. Several integrin subunits including α2, α5, β1 and β3 were identified in the periodontal tissue [18,34]. Given the interplay of integrins with the extracellular matrix (ECM) and cytoskeleton [35], they regulate cellular functions, cell proliferation, adhesion, shape, and differentiation [32].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro observation showed the presence of integrin subunits in human gingival fibroblasts (HGFs) and the morphological alteration of HGFs due to the surface roughness of Ti [18]. Surface topography is an important factor in cell attachment, adhesion, proliferation, and differentiation [19], which also affects cell orientation and migration [20].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, PDL fibroblasts display increased spreading on smooth rather than SLA titanium surfaces 37 . Gingival fibroblast attachment to smooth rather than SLA surfaces and smooth titanium surfaces enhanced expression of the ECM receptors, integrin α4 and β1 subunits 38 . PDL cell attachment to all types of titanium surfaces is inhabited by antibodies to the integrin β1 subunit (common to several ECM receptors) and arginine‐glycine‐aspartic acid–containing peptides (the common integrin binding site for fibronectin, fibrinogen, and many other ECM molecules) 39 .…”
Section: Discussionmentioning
confidence: 93%
“…One established solution is the development of adjusted Ti/Nb/Zr/Sn titanium alloys whose Young’s modulus is close to the physiological Young’s modulus of approximately 50 GPa [91]. Two attractive functionalization procedures have been described, first the immobilization of the surface with RGD-ligands [92] and second, tailoring/patterning the surface of the titanium material with nano-spikes which fit in the architectural arrangement of the integrin receptors of the bone cells by which a functional morphology and an expression of growth factors in bone cells are elicited [93]. …”
Section: Scaffoldmentioning
confidence: 99%